Towards developing a Teddy Bear Therapy Training Programme for Psychotherapists - van der Ryst, L. (University of Limpopo (Medunsa Campus), 2012)
Teddy Bear Therapy is a specialised type of intervention which calls for effective training oftherapists interested in conducting Teddy Bear Therapy. However, no structured training programme for psychotherapists in this child therapy exists to this date. The current study therefore developed a training programme for psychotherapists in Teddy Bear Therapy. The investigation was done by using a qualitative, descriptive research design. This allowed for a systematic description of the nature of child psychotherapy training programmes by means of a narrative literature review. From the literature review, questions were derived to be used in semi-structured interviews with three clinical psychologists. The data obtained from the interviews were analysed and common themes identified. These findings were combined with the data obtained from the literature review. This integration resulted ina training programme in Teddy Bear Therapy. The training programme incorporates theoretical as well as experiential learning. The programme outline provides the facilitator with clear instructions as to what each session's objectives and tasks are. The trainee is provided with a manual that firstly provides background information necessary to understand the application of Teddy Bear Therapy. Secondly, the manual provides specific information on the development and process of Teddy Bear Therapy. The trainee must work through the manual, do exercises, take part in discussions or prepare readings whenever indicated to do so by the facilitator. In spite of the contribution which the training programme and its manual can make to the South African context, it is limited to the theoretical framework of a dissertation and has not yet been implemented or empirically tested.
Thesis(MSc (Clinical Psychology)) -- University of Limpopo, 2012.
Keywords: Teddy bear therapy; Psychotherapy